2013
DOI: 10.1080/02640414.2013.773404
|View full text |Cite|
|
Sign up to set email alerts
|

Changes in the redox status and inflammatory response in handball players during one-year of competition and training

Abstract: The present research was designed to evaluate the adaptive responses to oxidative stress and inflammation in handball players subjected to well-controlled training intervals over one-year of competition. Seven blood samples were collected over the season of the study, approximately one a month. Plasma lipid peroxidation, nitrite, cytokines (IL-1β, IL-6, INFγ and TNFα), and the glutathione cycle in erythrocytes, were measured. Exercise intensity, measured with the Borg's scale, increased significantly up to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 43 publications
1
13
0
Order By: Relevance
“…Increased inflammatory reactions in response to increasing training loads have been reported by some authors in handball and cycling athletes [10] while others did not find any significant alterations in inflammatory mediators during preseason training in sports teams [1,3,39]. IL-1β and TNF-α are the most important inflammatory cytokines, specifically in the early phases of the inflammatory process, and increased circulating levels can be observed in some athletes after intense or high volume exercises, such as reported during official competitions [9,40].…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…Increased inflammatory reactions in response to increasing training loads have been reported by some authors in handball and cycling athletes [10] while others did not find any significant alterations in inflammatory mediators during preseason training in sports teams [1,3,39]. IL-1β and TNF-α are the most important inflammatory cytokines, specifically in the early phases of the inflammatory process, and increased circulating levels can be observed in some athletes after intense or high volume exercises, such as reported during official competitions [9,40].…”
Section: Discussionmentioning
confidence: 90%
“…After a period of single or multiple exposures to highintensity exercise, increased circulating levels of soluble muscle damage biomarkers such as lactate dehydrogenase and creatine kinase (in addition to inflammatory markers such as pro-inflammatory cytokines and C-reactive protein) are evident [9,10]. This is mainly observed in response to eccentric exercise [11][12][13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, a similar plasma redox profile has recently been reported in professional adult handball players undergoing 1 year of competition and training. The lack of hyperoxidative state that normally follows high-intensity exercise in athletes was considerably associated with their adaptation to exercise-induced ROS production, as well as specifically designed training periodization [28]. Nevertheless, the implications of the current findings of an increase in post-exercise serum XO activity (associated with potential insufficiency of the antioxidant defense system) should not be neglected.…”
Section: Resultsmentioning
confidence: 99%
“…Markers of oxidative stress may be important parameters of biological monitoring of athletes (6). Studies that have explored the redox state in athletes during the competitive season have shown that the antioxidative status changes depending on the training load and training phase (7)(8)(9)(10)(11)(12)(13). Periods of intensive training may lead to a decrease in antioxidative capacity and a consequent increase in oxidative stress.…”
Section: Introductionmentioning
confidence: 99%